PENGARUH MOTIVASI TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII UPTD SMP N 1 KEC. KAPUR IX - Nabilla Ayunda (Departemen Matematika, 2020)
This research is intended to know how much correlation between learning motivation and mathematics learning outcomes of grade VIII at UPTD SMP N 1 Kec. Kapur IX. Learning outcomes are a reference to see whether or not the goals of learning have been achieved. Learning motivation is one thing that affects learning outcomes. Motivation is an energy that can trigger mind and body to do something. It means, if students have motivation to learn, students will get good learning outcomes. In this study, a correlation approach was used that look for the influence of one variable on other variables. The data analysis obtained from this study are at a significance of 5% indicate that r count is greater than r table (0.778> 0.273) which means that learning motivation has an influence on learning outcomes as much as 60%. Keywords: Descriptive Research, Learning Motivation, Learning OutComes